Peranan Profesi dan Pengamanan (Propam) dalam Penegakan Hukum Tindak Pidana Penyalahgunaan Narkotika yang Dilakukan oleh Anggota Kepolisian di Wilayah Hukum Kepolisian Resor Siak - Christina Magdalena; Erdianto '; Mukhlis ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Narcotic crime is a very complex issue because it is a disease that is very difficult to eradicate. Often these violations committed by law enforcement officials which should be the main pillar in law enforcement. In narcotic crime accountability sanctions imposed as a punishment for his actions. As for the purpose of this thesis, namely: First, to determine the role of Profession and Security (Propam) in criminal law enforcement narcotics abuse committed by members of the police in the jurisdiction of Police Siak. Second, to determine the obstacles encountered by Profession and Security (Propam) in criminal law enforcement narcotics abuse committed by members of the police in the jurisdiction of Police Siak. Third, to determine the efforts made to overcome the obstacles encountered by Profession and Security (Propam) in criminal law enforcement narcotics abuse committed by members of the police in the jurisdiction of Police Siak.This type of research is juridical sociological research, ie research on the location or place directly studied. This research was conducted in the jurisdiction of Police Siak. While the overall population and the sample is related to the problem under study. Source of data used are primary data and secondary data. Data collection techniques in this study is a questionnaire, interviews and literature study. From the research it can be concluded that: First, the role of Profession and Security (Propam) in criminal law enforcement narcotics abuse committed by members of the police in the area of Police Law Siak services include public complaints about irregularities behavior and actions of police personnel, discipline, order and internal security personnel, implementation of the disciplinary hearing and the professional code of ethics and professional breeding personnel, supervision and assessment of personnel who are and have been running the disciplines of law and / or code of professional conduct, as well as the issuance of rehabilitation personnel who have carried out the punishment and not guilty of the offense discipline and / or code of conduct. Secondly, constraints such as lack of cooperation with the community, emotional connection and personal relationships that often occur, which tend personality apparatus poor, and lack of facilities and infrastructure. Third, efforts, among others, counseling or seminars to the public, any investigation conducted by the police, accompanied by members of higher rank, penghimbauan to all members of the police were able to continue their education at least up to Tier-1 (S1), as well as maximizing existing facilities and infrastructure.Keywords: Role - law enforcement - criminal offenses - drug abuse - a member